National Originality And Interlingual Connections Of Phraseologies In Russian And Uzbek Languages (Open Academia: Journal of Scholarly Research, 2024)
This article explores the complex interplay between national originality and interlingual connections in the phraseological systems of Russian and Uzbek languages. Phraseology serves as a rich repository of cultural values, historical narratives, and social norms, reflecting the unique identity of each nation. By examining various phrases and idiomatic expressions in both languages, the study highlights how these expressions encapsulate national characteristics while also revealing the influence of intercultural communication and historical interactions. The article employs a comparative analysis, identifying parallels and divergences in phraseological constructs, and discusses the implications for language acquisition, translation, and cultural exchange. Ultimately, this research aims to enhance our understanding of how phraseology functions as a bridge between languages, enriching both linguistic heritage and cultural dialogue